Atomic‐Scale Metal–Insulator Transition in SrRuO3 Ultrathin Films Triggered by Surface Termination Conversion. Issue 8 (12th December 2019) - Lee, Han Gyeol; Wang, Lingfei; Si, Liang; He, Xiaoyue; Porter, Daniel G.; Kim, Jeong Rae; Ko, Eun Kyo; Kim, Jinkwon; Park, Sung Min; Kim, Bongju; Wee, Andrew Thye Shen; Bombardi, Alessandro; et al.
Abstract: The metal–insulator transition (MIT) in transition‐metal‐oxide is fertile ground for exploring intriguing physics and potential device applications. Here, an atomic‐scale MIT triggered by surface termination conversion in SrRuO3 ultrathin films is reported. Uniform and effective termination engineering at the SrRuO3 (001) surface can be realized via a self‐limiting water‐leaching process. As the surface termination converts from SrO to RuO2, a highly insulating and nonferromagnetic phase emerges within the topmost SrRuO3 monolayer. Such a spatially confined MIT is corroborated by systematic characterizations on electrical transport, magnetism, and scanning tunneling spectroscopy. Density functional theory calculations and X‐ray linear dichroism further suggest that the surface termination conversion breaks the local octahedral symmetry of the crystal field. The resultant modulation in 4d orbital occupancy stabilizes a nonferromagnetic insulating surface state. This work introduces a new paradigm to stimulate and tune exotic functionalities of oxide heterostructures with atomic precision. Abstract : An atomic‐scale metal–insulator transition triggered by surface termination conversion in SrRuO3 ultrathin films is demonstrated. A water‐leaching method enables uniform and effective termination engineering at the SrRuO3 (001) surface. As the surface termination converts from SrO to RuO2, a highly insulating and nonferromagnetic phase emerges within the topmost SrRuO3 monolayer due to the broken octahedral symmetry resulting in insulating orbital occupancy.